2021
DOI: 10.3389/fcell.2021.799049
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125 Family in Cardiovascular and Cerebrovascular Diseases

Abstract: Cardiovascular and cerebrovascular diseases are a serious threaten to the health of modern people. Understanding the mechanism of occurrence and development of cardiovascular and cerebrovascular diseases, as well as reasonable prevention and treatment of them, is a huge challenge that we are currently facing. The miR-125 family consists of hsa-miR-125a, hsa-miR-125b-1 and hsa-miR-125b-2. It is a kind of miRNA family that is highly conserved among different species. A large amount of literature shows that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Exosome contains not just a variety of proteins, it also encapsulates genetic substances. MicroRNA sequencing disclosed more than 400 total miRNAs, specifically including those associated with oxidation regulation, vascular calcification, and SMCs’ plasticity (mir-125 family, mir-143), anti-inflammation (mir-16–5p), tissue repair (let-7 family), and cholesterol hemostasis (mir-26, mir-148) (Figure H). These results suggested that MSCs-Exo was successfully extracted, and it conveys contents that have the potential to regulate efferocytosis process, lipid metabolism, SMCs’ phenotype transformation, and oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Exosome contains not just a variety of proteins, it also encapsulates genetic substances. MicroRNA sequencing disclosed more than 400 total miRNAs, specifically including those associated with oxidation regulation, vascular calcification, and SMCs’ plasticity (mir-125 family, mir-143), anti-inflammation (mir-16–5p), tissue repair (let-7 family), and cholesterol hemostasis (mir-26, mir-148) (Figure H). These results suggested that MSCs-Exo was successfully extracted, and it conveys contents that have the potential to regulate efferocytosis process, lipid metabolism, SMCs’ phenotype transformation, and oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified six miRNAs including miR-125a-5p, miR-125b-5p, miR-181b-5p, miR-19a-3p, miR-20a-5p, and miR-30b-5p were significantly associated with heart failure (HF) ( Supplementary Table 4 ). Of these six miRNAs, the miR-125 family was previously reported to be dysregulated and significantly correlated with HF and many other cardiac manifestations ( 12 , 33 35 ). Also, miR-19, miR-181, miR-125, and miR-30 levels were associated with myocardium levels during the development of diabetic cardiomyopathy and failing hearts ( 33 , 36 ), and the miR-30 and miR-19 families were frequently reported to be dysregulated in patients with the acute coronary syndrome (ACS) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic cell death is linked to low expression of miR-498 in MI patients [47] and is in agreement with the downregulation in our array. MiRNAs with a negative correlation between cardiac remodeling and the direction of regulation in our array, such as miR-28 [48,49], miR-374c [50], and miR-125a [51] are likely part of an early coping mechanism.…”
Section: Microrna Regulation In Stretch Versus Tachycardia Induced Re...mentioning
confidence: 96%